2010
DOI: 10.1159/000281015
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a), Birth Weight and Neonatal Stroke

Abstract: Background: Elevated lipoprotein (Lp) (a) is the most common genetically determined risk factor found in babies with perinatal ischemic stroke. The influence of maternal Lp(a) has not been studied extensively to date. Objectives: To investigate the role of Lp(a) in our population of neonates with stroke. Methods: In a prospective uncontrolled cohort of term-born children with neonatal arterial ischemic stroke, Lp(a) levels were investigated in 69 mothers and 69 children. Paternal Lp(a) was not explored. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Interestingly, in a French study of mother-infant diads of neonatal AIS, elevated maternal Lp(a) was not only implicated in perinatal AIS but also correlated with low birth weight in these infants, leading to a hypothesis that elevated Lp(a) may mediate placental insufficiency. 18 With regard to recurrent AIS in childhood, a prospective multicenter cohort study in Germany 13 demonstrated that Lp(a) >30 mg/dL was an independent risk factor for recurrent AIS (OR: 2.8; 95% CI: 1.1-7.5).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a French study of mother-infant diads of neonatal AIS, elevated maternal Lp(a) was not only implicated in perinatal AIS but also correlated with low birth weight in these infants, leading to a hypothesis that elevated Lp(a) may mediate placental insufficiency. 18 With regard to recurrent AIS in childhood, a prospective multicenter cohort study in Germany 13 demonstrated that Lp(a) >30 mg/dL was an independent risk factor for recurrent AIS (OR: 2.8; 95% CI: 1.1-7.5).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the demonstrated increased risk of AIS in children with elevated maternal Lp(a) may be mediated through impaired vascular placental function. 55 In another study involving 60 mother-child pairs, a statistically significant difference (p < 0.0001) was observed between the general population and mothers of children with perinatal arterial stroke with regard to elevated serum Lp(a) levels, among other prothrombotic factors. In addition, in this study, 33% of mothers and 21% of children with perinatal AIS presented elevated Lp(a) levels.…”
Section: Lp(a) and Cerebrovascular Accidentsmentioning
confidence: 93%
“… 137 Of note, the risk of hemorrhagic stroke is reduced in patients with high Lp(a) levels. 138 Lp(a) is a particularly strong predictor of ischemic stroke in neonates, 139 children, 140 , 141 and young adults. 142 Children with high Lp(a) levels have a 4-fold risk of ischemic stroke with an even higher risk for recurrent stroke.…”
Section: Lp(a) and Non-coronary Diseasesmentioning
confidence: 99%